Coaxially swirled porous disks flow simultaneously induced by mixed convection with morphological effect of metallic/metallic oxide nanoparticles - Raza, Qadeer; Wang, Xiaodong; Hassan, Ahmed M.; Siddique, Imran; Ali, Bagh; Ali, Irfan (Frontiers in Materials, 2023)
This study focuses on the numerical modeling of coaxially swirling porous disk flow subject to the combined effects of mixed convection and chemical reactions. We conduct numerical investigations to analyze the morphologies of aluminum oxide (Al2O3) and copper (Cu) nanoparticles under the influence of magnetohydrodynamics. For the flow of hybrid nanofluids, we developed a model that considers the aggregate nanoparticle volume fraction based on singlephase simulation, along with the energy and mass transfer equations. The high-order nonlinear ordinary differential equations obtained from the governing system of nonlinear partial differential equations via similarity transformation. The resulted system of ordinary differential equations are solved numerically by Runge-Kutta technique and the shooting method. It is one of the most widely used numerical algorithms for solving differential equations in various fields, including physics, engineering, and computer science. This study investigated the impact of various nanoparticles shapes factors (Spherical, Platelet and Laminar) subject to relevant physical quantities and their corresponding distributions. Our findings indicate that aluminum oxide and copper (Al2O3-Cu/H2O) hybrid nanofluids exhibit significant improvements in heat transfer compared to other shape factors, particularly in laminar flow. Additionally, the injection/suction factor influences the contraction/expansion phenomenon, leading to noteworthy results concerning skin friction and the Nusselt number in the field of engineering. Moreover, the chemical reaction parameter demonstrates a remarkable influence on Sherwood's number. The insights gained from this work hold potential benefits for the field of lubricant technology, as they contribute valuable knowledge regarding the behavior of hybrid nanofluids and their associated characteristics.